Diferencias en el efecto antioxidante y neuroprotector de hidroxitirosol en la diabetes mellitus experimental respecto a una situación de normoglucemia - Villanueva Torres, Beatriz (UMA Editorial, 2016)
The aim of this study is to assess whether the administration of hydroxytyrosol (HT) to diabetic animals exerts a neuroprotective effect on brain damage in a model of hypoxia-reoxygenation. Rats (10 per group) were distributed in five groups: nondiabetic rats, control diabetic rats (DR), DR rats treated two months with 1, 5 or 10 mg/kg/day p.o. HT. At the end of follow-up an experimental model of hypoxia-reoxygenation in brain slices was carried out. DR showed increased cell death, oxidative and nitrosative stress and an increase in brain inflammatory mediators. All these alterations were significantly higher in DR than normoglycemic. HT significantly reduced oxidative and nitrosative stress and brain inflammatory mediators production. Cell death was reduced by 25.9%, 37.5% and 41.0% after the administration of 1, 5 or 10 mg/kg/day. In conclusion we provide the neuroprotective effect of the administration of HT in experimental diabetes.
Keywords: Polifenoles; Tesis doctoral; Diabetes experimental; Hidroxitirosol; neuroprotección